120TiPEORTC SPECTA-AYA: A molecular profiling platform for adolescents and young adults with cancer in Europe. (7th November 2019) - de Rojas, T; Kasper, B; Van der Graaf, W; Pfister, S M; Bielle, F; Ribalta, T; Shenjere, P; Preusser, M; Fröhling, S; Morfouace, M; McCabe, M G
Abstract: Background: For most adolescent and young adult (AYA) cancers, age-specific molecular features are poorly understood. SPECTA, an academic translational research infrastructure for biomaterial collection and molecular analysis, will explicitly recruit AYA patients and will therefore collect empirical data to bridge the molecular gap between pediatric and adult oncology. Trial Design: The initial pilot study, activated in February 2019 across Europe, will recruit 100 patients aged 12-29 years with newly diagnosed or relapsed high-grade gliomas and high-grade bone and soft tissue sarcomas. The primary objective of the pilot is to determine feasibility and recruitment rates. Formalin-fixed tumor tissue, whole blood and clinical data from study participants will be prospectively collected; the biomaterial will be stored centrally at the Integrated BioBank of Luxembourg (IBBL). Whole exome sequencing (WES) of matched tumor and blood, and tumor RNA sequencing and DNA methylation profiling will be performed at the German Cancer Research Center (DKFZ), Heidelberg. Virtual central pathology review of scanned diagnostic slides will be undertaken by an international expert panel, and diagnostic material returned to the participating centers. A multidisciplinary molecular tumor board will release a clinically validated report to referring clinicians within 4-6 weeks after biopsy. SPECTA-AYA constitutes a major opportunity to gain knowledge about the tumor biology of this unique age group. It incorporates notable innovative aspects: AYA specificity, pan-European academic collaboration, centralized biobanking, comprehensive molecular profiling, and virtual central pathology review, among others. SPECTA-AYA will help untangle the tumor particularities of AYAs with cancer and aims to improve their access to novel drugs and personalized medicine. Legal entity responsible for the study: EORTC (European Organisation for Research and Treatment of Cancer). Funding: Walgreens Boots Alliance. Disclosure: W. Van der Graaf: Research grant / Funding (self): Novartis; Honoraria (institution), Advisory / Consultancy: Bayer. F. Bielle: Research grant / Funding (self), Shareholder / Stockholder / Stock options, Spouse / Financial dependant: Celgene; Research grant / Funding (self), Shareholder / Stockholder / Stock options, Spouse / Financial dependant: Crossject; Research grant / Funding (self), Shareholder / Stockholder / Stock options, Spouse / Financial dependant: Sanofi; Research grant / Funding (self), Shareholder / Stockholder / Stock options, Spouse / Financial dependant: AbbVie. M. Preusser: Honoraria (self): Bayer; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Novartis; Honoraria (self): Gerson Lehrman Group (GLG); Honoraria (self): CMC Contrast; Honoraria (self): GlaxoSmithKline; Honoraria (self): Mundipharma; Honoraria (self): Roche; Honoraria (self): Astra Zeneca; Honoraria (self): AbbVie; Honoraria (self): Lilly; Honoraria (self): Medahead; Honoraria (self): Daiichi Sankyo; Honoraria (self): Merck Sharp & Dohme. S. Fröhling: Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self), Travel / Accommodation / Expenses: Amgen; Honoraria (self), Travel / Accommodation / Expenses: Eli Lilly; Honoraria (self), Research grant / Funding (self), Travel / Accommodation / Expenses: PharmaMar; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Pfizer. M.G. McCabe: Advisory / Consultancy: Ipsen Pharma. All other authors have declared no conflicts of interest.